Alternative grafts for brachioaxillary hemodialysis access: 1-year comparative results - Belczak,Sergio Quilici (2015)
BACKGROUND: Many chronic renal patients lack autologous veins in the upper limbs suitable for construction of arteriovenous fistulas for hemodialysis. Alternative fistula options for these patients should be evaluated and compared.OBJECTIVE: To compare different types of grafts used for brachioaxillary access in hemodialysis patients in terms of their patency and complication rates.METHOD: Forty-nine patients free from arterial system abnormalities and with no venous options for creation of arteriovenous fistulae in the arm and/or forearm underwent brachioaxillary bypass with implantation of autologous saphenous vein, polytetrafluoroethylene (PTFE), or PROPATEN(r) grafts. Patients were assessed by Doppler ultrasonography at 3, 6, and 12 months after surgery,.RESULTS: The four first saphenous vein grafts had failed by 3 or 6 months after surgery. The autologous saphenous vein group was discontinued at the beginning of the study because of extreme difficulty in achieving puncture and hematoma formation. Failure rates of PTFE and PROPATEN(r) grafts did not differ after 3 (p = 0.559), 6 (p = 0.920), or 12 months (p = 0.514). A log-rank test applied to cumulative survival of grafts at 1 year (0.69 for PTFE, 0.79 for PROPATEN(r)) detected no significant differences (p = 0.938). There were no differences in complications resulting in graft failure between the two types of prosthetic graft.CONCLUSION: Autologous saphenous vein grafts do not appear to be a good option for brachioaxillary hemodialysis access because of difficulties with achieving puncture. Brachioaxillary fistulae constructed using PTFE or PROPATEN(r) grafts exhibited similar patency and complication rates. Further studies with large samples size are warranted to confirm our findings.